Perceptions and Attitudes of Women of Childbearing Age towards Cervical Cancer Screening: A Psychological Review - Ainun Ganisia; Rakhmalia Imeldawati; Nurul Fathiyyah; Cityta Putri Kwarta (The Indonesian Institute of Science and Technology Research, 2025)
In Indonesia, cervical cancer ranks as the second leading cause of death among women, coming in right after breast cancer, which holds the top spot. Early detection or screening is the primary modality carried out to overcome the high rate of cervical cancer deaths in Indonesia, but the number of screening participants is still low. One of the causes is the perception of women of childbearing age towards cervical cancer. This study aimed to explore the connection between the perceptions and attitudes of women of childbearing age towards cervical cancer screening. The research method used a cross-sectional design with a population of women aged 20-50 years in Sukorambi Village, Jember Regency. A total of 86 participants were involved, chosen through a cluster random sampling method. The findings revealed that the respondents' mean age was 34.66 year, with the majority having a high school education (62.80%), the majority being unemployed (72.09%), and the majority being married (95.35%). The outcomes of the data evaluation indicated a p-value of 0.002, which is less than 0.05, along with a correlation coefficient of 0.324. This leads to the conclusion that a significant connection exists between perceptions and attitudes towards cervical cancer screening among women of childbearing age in Sukorambi Village. In increasing awareness of WUS, it is hoped that health workers will actively and routinely hold cervical cancer screening socialization activities to influence WUS attitudes towards cervical cancer screening.